2021
DOI: 10.13031/aea.14255
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Optimal Threshold of Water and Nitrogen Quantities for Tomato Growth under the Irrigation with Biogas Slurry in Greenhouse

Abstract: HighlightsApplication of biogas slurry can significantly improve the integrated growth, yield, quality of tomatoes.Water-nitrogen coupling model was established based on multi-index evaluation system of tomatoes.The optimal application quantitative range of water and nitrogen was obtained based on the water-nitrogen coupling model.Abstract. Biogas slurry, a liquid organic fertilizer, has been widely used in agricultural production. However, the characteristics of high water content and low fertility make it al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This is consistent with the relevant results obtained by Du et al [39] , Wang et al [40] , and by Zheng et al [11] . TOPSIS method has been proven to be a good evaluation method in agricultural production [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the relevant results obtained by Du et al [39] , Wang et al [40] , and by Zheng et al [11] . TOPSIS method has been proven to be a good evaluation method in agricultural production [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the application of biogas slurry in agriculture production can significantly increase soil organic matter content [7] , improve crop quality [8] , maintain soil fertility [9] , and facilitate the formation of soil aggregate structure. Nevertheless, biogas slurry is a mass with high water content and low fertility [10] , making it easy to produce surface runoff or deep leakage when applied by traditional irrigation methods, which will reduce the water and fertilizer use efficiency.…”
Section: Introduction mentioning
confidence: 99%
“…The consistency test coefficients were CR < 0.1, indicating that the consistency met the requirements. In Table 10, the objective weights of each evaluation indicator were calculated using the entropy weight method (EWM) based on the tomato quality indicators, nitrogen utilization, and growth benefits, while the indicator matrix was constructed [25]. Simultaneously, to achieve more scientific and reasonable weights, the combined weights were calculated using AHP and EWM.…”
Section: ( )/( )mentioning
confidence: 99%